CHALLENGES AND OPPORTUNITIES OF TEACHING ACADEMIC WRITING SKILLS: A CASE STUDY OF STUDENTS AT IAIN KUDUS - Sri Wahyuningsih (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This article aims at exploring some possible challenges of opportunities of teaching English in academic writing skills for Indonesian learners at IAIN Kudus. The study anchors in a qualitative research. The observation, interview and documentation are conducted to gather data. The result indicates that numerous challenges faced by some learners from English Department at IAIN Kudus in the academic writing includes the difficulties of how to start writing, lack of both intensive and extensive reading, limited exposures to English vocabularies, and lack of interest in writing English. Besides, the opportunities that could be exposed to enhance the process of teaching academic writing skills among learners from English Department at IAIN Kudus are by sharpening their receptive skills such as reading and listening in order to gain successful productive skills including speaking and writing, asking them to be aware of paraphrasing English texts precisely, pursuing them to apply reference management tools properly in quoting a number of references comprising of books, journal articles, and so forth, using technology or digital tools such as instagram, facebook, blog, and so forth to enhance the process of teaching academic writing skills and pursuing them to take part in academic writing workshop and seminar.